PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS V - Qathrun Nada Fitria; Aisyah Ma’wiyah; Nur Azmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The learning of Indonesian language in elementary schools continues to face challenges, particularly the low level of students' learning outcomes due to the predominance of conventional teaching methods that provide limited opportunities for active student engagement. This study aimed to determine the effect of the Problem Based Learning (PBL) model on improving the Indonesian language learning outcomes of fifth-grade students at SD Negeri 3 Banda Sakti in the 2025/2026 academic year. The study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 40 students, including 20 students in the experimental class and 20 students in the control class. Data were collected through pretest and posttest learning achievement tests and analyzed using normality, homogeneity, and Independent Samples t-test with the assistance of SPSS software. The results showed that the average pretest score of the experimental class increased from 65.0 to 91.0 on the posttest, while the average score of the control class increased from 66.5 to 80.5. The greater improvement in the experimental class indicates that the implementation of the Problem Based Learning model had a positive effect on students' Indonesian language learning outcomes. Therefore, the Problem Based Learning model can be considered an effective instructional alternative for improving both the quality of the learning process and students' learning outcomes in Indonesian language subjects at the elementary school level.